Impact of Intangible Assets on Competitive Positions of the Apple Company - DANKO, T. P.; VYAZOVIKOVA, A. S.; KISELEV, V. M.; RAUSKIENE, Ona; KLIMENKO, O. I.; SEMENOVA, G. N.; SEKERIN, V. D. (Journal of Advanced Research in Law and Economics, 2019)
Urgency of the study: The urgency of this study is substantiated by the problem on the reliability of assessing the value of intangible assets and their impact on the competitive position of the company in the ratings of high-tech companies operating in the international segment of the IT market. The study was aimed at assessing the impact of the value and structure of intangible assets of the Apple company (Apple) on its position as compared to its closest competitors of the global IT market: Microsoft, Google, Facebook, and Amazon. The basic study method has been the market review of the global IT market in the segment of intangible assets owned by leading high-tech companies. The study has used the methods of competitive analysis, rating positioning, assessment of intangible assets, portfolio matrices, as well as the correlation and regression analysis. The competitive analysis of Apple and its closest competitors – Microsoft, Google, Facebook, and Amazon – has been carried out on the parameters of comparing the value of brands, intangible assets, and their share in the market value of the companies by using ratings of Interbrand, Boston Consulting Group, and Brand Finance. The ratio of tangible and intangible assets of Apple and its competitors and the distribution of intangible assets by the criterion of accounting in the balance sheets of companies have been assessed. The structure of intangible assets has been studied by sources of formation (marketing, contractual assets, consumers, technologies, and goodwill), and the matrices for their distribution in the Apple’s and its competitors’ portfolio have been formed. The models of the regression dependence of the market value and the Apple’s sales revenue on the value of intangible assets have been formed. The results of the study analytically confirm the hypothesis about the impact of intangible assets on the company’s competitive position in international ratings of high-tech companies in the IT market, the company’s market value, and sales revenue. The materials of the article can be useful for marketing analysts who study the impact of intangible assets on the competitive positions of high-tech companies in the IT market.